Status of Research on Variation of Strength of Timber in India - Rajput, S. S.; Shukla, N. K. (Indian Forester, 1992)
Briefly bringing out the importance of research on variation of strength of timber, the results of studies undertaken on between and within species variation of properties of Indian timbers have been briefly presented and discussed. It has been emphasised that while knowledge of between species variation is necessary for rational classification and utilisation of different timbers for various end uses, the knowledge of within species variation is important for proper grading and selection of material.